Dakwah Transformatif Menciptakan Karakter Pemuda Islami (Studi Kasus Majelis Gaul Jember) - Nur Kamilah (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2021)
There has been a spreading phenomenon in which many of today's youth societies tend to go wild and out of control. Most of such functions tend to be surrounded by individuals who indulge themselves in sinful acts instead of doing a self-discovery process to gain the God's blessings. Having seen many youths tend to enjoy doing forbidden acts and restrain-free activities, therefore Majlis Gaul community proposed a new way of da'wah. The community employs a subtle and a heart warming way of conveying da'wah. It is no longer conventional preaching which is in the form of oral da'wah, but they employ transformative da'wah method. This transformative da'wah is implemented in social change activities, by using da'wah as a religious material and positioning the dai (preacher) as the conveyer of religious messages to the community. The current study is a qualitative research with descriptive qualitative approach. In this study, the data are presented in descriptive texts. The results of this study are: 1) In shaping the Islamic character, Majlis Gaul community held a